What are the features of abusive abdominal injury? a systematic review. (29th September 2015) - Haroon, M; Mann, M; Tempest, V; Lumb, R; Kemp, A; Maguire, S
Abstract : Aims: Abusive abdominal injuries carry significant morbidity and mortality, yet are rarely recognised. The authors aim to determine the prevalence and characteristics both clinically and biochemically. Methods: The authors performed a literature search of databases, websites and references from 1950 to 2009. Of 2352 abstracts, 180 studies underwent two independent reviews using standardised criteria, with a third review if there was disagreement. Inclusion criteria: primary studies of children <18 years with confirmed abuse (abuse rank 1–3), injury confirmed by CT/contrast studies/laparotomy/postmortem. Exclusion criteria: anogenital injuries, solely management/outcome studies, accidental injuries alone. Where appropriate, a random effects proportion meta-analysis was performed. Results: Overall, 58 studies (854 children; 103 with abusive abdominal injuries) were included. Of these, <10% (range 0.5–0%) of abused children sustained abdominal injuries, with a mortality of 30–47%. The commonest injuries were to the bowel (pooled proportion=0.45) and liver (0.48), predominantly affecting small bowel. Accidental bowel injuries (from falls) did not occur in children <5 years (mean age of children admitted with visceral injuries due to falls=10.39 years, mean age of visceral injury due to abuse=3.73 years). Common symptoms included vomiting (bilious and non-bilious), abdominal distension and tenderness; while bruising elsewhere on the body was frequently present, abdominal bruising was often absent (40–90% of cases). Coexistent fractures were recorded in 27–35% of cases. Three studies evaluated the diagnostic utility of alanine transaminase (ALT)/aspartate transaminase (AST) for liver trauma associated with abuse. Varying cutoffs were suggested as indicating liver trauma including AST:ALT>1. Conclusion: Abdominal injury should be considered in any physically abused child, as symptoms may be non-specific. The absence of local bruising does not preclude significant injury. Small bowel injuries in young children have a strong association with abuse, but liver injury is also common. Measurement of AST and ALT may assist in assessing for occult abdominal injury and may be useful prognostically.